Enhancing activity of β-lactam and fluoroquinolones antibiotics by artemisinin and its derivatives against MDR Escherichia coli - Ul Haq, Shahbaz; Wang, Ling; Guo, Wenzhou; Aqib, Amjad Islam; Muneer, Afshan; Saqib, Muhammad; Ahmad, Saad; Ghafoor, Muzafar; Iftikhar, Amir; Chen, Keyuan; Liang, Jianping (Frontiers in Veterinary Science, 2022)
Artemisinin and its derivatives had played a biocidal role in biomedical remedies, while they were expected to enhance the activity of antibiotics against multiple drug-resistant (MDR) bacteria. The current study evaluated the interaction of artemisinin (ART), dihydroartemisinin (DHA), artesunate (AS), and artemisinic acid (AA) with β-lactam and fluoroquinolones antibiotics against Escherichia coli. Antibiotic strip test (E-test), Kirby Bauer's disc test (KB method), and broth microdilution method were adopted for susceptibility analysis, while the checkerboard method was applied to assess synergisms. ART, DHA, AS, and AA showed significantly enhanced antibacterial effects of β-lactam antibiotics against different strains of E. coli. The study showed ciprofloxacin to be most effective by presenting the least MIC (0.017125 ± 0.0022 μg/ml), while oxacillin was least effective (MIC 256 μg/ml) against E. coli. Synergism between AA and penicillin G (75%), ampicillin (25%), and oxacillin (50%) was observed in all isolates tested. AA and AS significantly decreased the MIC of ampicillin (−0.912 ± 0.908 μg/ml) and ciprofloxacin (−0.901 ± 0.893 g/ml), respectively. Artemisinin and its derivatives increased antibiotic accumulation within E. coli in a dose-dependent manner. The time-kill assay significantly reduced the bacterial number within 24 h of incubation. The study thus concludes greater room for improvement in enhancing the efficacy of antibiotics if used with artemisinin and its derivatives.